MANAJEMEN TAMAN PENDIDIKAN AL-QUR'AN DI LEMBAGA KOORDINASI GERAKAN TAMAN PENDIDIKAN AL-QUR'AN SOLO TAHUN 2017 - Wicaksono, Khairu Wirawan (El-Hayah, 2018)
Abstract:The findings about the presence of TPQ in some areas in solo that goes without a definite curriculum in its implementation becomes the background of this research. For unstructured curriculum of non-formal TPQ institutions, Institution of Coordination for Movement of Al-Qur'an Education Solo tries to provide solutions by creating a curriculum that can be applied by TPQ in each region. This issue is interesting enough to be examined because curriculum made by that institution gives solution for TPQ manager to manage institutionwell. This research used descriptive qualitative approach. This research was conducted at Institution of Coordination for Movement of Al-Qur'an Education and several TPQ in Solo that have been employed curriculum of LKG TPQ. Subject of this research was the chairman of LKG, while informants were the chairman of TPQ and TPQ teachers. Instrument of this research was the writer. Technique of collecting data used observation, interview and documentation. Technique of data analysis used data collection, data display, data reduction and conclusion using interactive analysis model.Â  This research shows that curriculum socialized by LKG TPQ can be a reference in implementing TPQ in Solo. For students, curriculum reference and books reference may create learning implementation in TPQ easier to be managed. It can be seen from interview results with some chairmen of TPQ accepting and joining curriculum socialization of LKG TPQ revealing that this curriculum is easier applied with detail guidance. Inhibiting factors in the curriculum implementation are lack of Human Resources in TPQ, so the curriculum implementation has not been maximal yet. Then, the follow up of curriculum socialization is still low, so some faced problems are not covered well. Â Keywords: Management, Qur'an Educational Park (TPQ)